A prospective study of maternal fatty acids, micronutrients and homocysteine and their association with birth outcome - Wadhwani, Nisha S. (Matern Child Nutr, 2013)
Our earlier studies both in animals and in humans have indicated that micronutrients (folic acid, vitamin B12) and long‐chain polyunsaturated fatty acids, especially docosahexaenoic acid (DHA), are interlinked in the one‐carbon cycle, which plays an important role in fetal ‘programming’ of adult diseases. The present study examines the levels of maternal and cord plasma fatty acids, maternal folate, vitamin B12 and homocysteine in healthy mothers at various time points during pregnancy and also examine an association between them. A longitudinal study of 106 normal pregnant women was carried out, and maternal blood was collected at three time points, viz., T1 = 16–20th week, T2 = 26–30th week and T3 = at delivery. Cord blood was collected at delivery. Fatty acids were estimated using a gas chromatograph. Levels of folate, vitamin B12 and homocysteine were estimated by the chemiluminescent microparticle immunoassay (CMIA) technology. Maternal plasma folate (P < 0.05), vitamin B12 (P < 0.01) and DHA (P < 0.05) levels were lowest, while maternal homocysteine levels were highest (P < 0.01) at T3. There was a negative association between maternal DHA and homocysteine at T2 (P < 0.05) and T3 (P < 0.01). There was a positive association between plasma DHA in maternal blood at T3 and cord blood. Furthermore, there was a positive association between maternal folate and vitamin B12 at T3 and baby weight, whereas maternal homocysteine at T1 were inversely associated with baby weight at delivery. Our study provides evidence for the associations of folic acid, vitamin B12, homocysteine with DHA and baby weight, suggesting that a balanced dietary supplementation of folate–vitamin B12–DHA during pregnancy may be beneficial.